The Important Place of Uzbek National Values and Nationality in Our Lives (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article hinglights the importance of our nationality and its role in our lives, Uzbek national values (traditions, foods, national costumes) and the roots of our Uzbekistan.